Coffee Culture Clash: Discovering Market Dynamics and Competition in Buraydah's Specialty Coffee - Kurniawan Arif Maspul (PT. Altaf Publishing Corp, 2024)
The specialty coffee industry in Buraydah, Al Qassim, Saudi Arabia, provides an enthralling atmosphere for research, with fierce rivalry and a strong coffee culture. To investigate the social, economic, and cultural aspects of the specialty coffee market in Buraydah, this study takes a multidisciplinary approach, merging ethnography, economics, sociology, marketing, and cultural studies. This extensive study adds to the comprehension of the specialty coffee market in Buraydah, with implications for stakeholders, policymakers, and the local population. It emphasizes the economic, social, and cultural forces that shape the sector, as well as the possibility for long-term success and beneficial influence through sustainable practices.